Theoretical Application of Salam Based into Agricultural Credit of Nigeria - Mohammed, Ahmed Ibrahim; Salisu, Yahuza; Uba, Rabiu (Kashere Journal of Management Sciences, 2024)
Agricultural credit is the catalyst of agricultural production especially in developing countries. It is also a machinery of sourcing fund for agricultural support for the generation of income and employment to the farmers. However, it has been indicated that the agricultural credit facilities given to the Farmers in most of the developing countries is inadequate and Nigeria is not in isolation. The decline of agricultural credit resulted in the emergence of poverty, food shortage and unemployment in Nigeria. Some researchers are of the view that insufficient credit facilities is among the major problem of Nigerian farmers. The main objective of this paper is to explore the role of Salam mode of financing as an alternative to the conventional agricultural credit in Nigeria. This paper established a relationship between the two variables, if validated in an empirical manner will hope to contribute to the growth of agriculture in Nigeria. Thus we seek to propose the utilization of Partial Least Square Structural Equation Modelling PLS in data analysis. This paper may highly contribute to decision and policy makers, farmers and free interest financial institutions and explore the advantages of Salam mode of financing as an alternative approach of agricultural credit policy in Nigeria